Analysis of Dental and Oral Health among Elementary School Students in The Working Area of Tembilahan Hulu Community Health Center - Dessica Noviasari; Doni Jepisah; Haili (LPPM Universitas Harapan Bangsa, 2024)
Dental and oral health is an integral part of overall body health. Having healthy teeth and mouth significantly helps in activities such as speaking, eating, and socializing without being disturbed by pain, discomfort, or embarrassment. However, the reality is that the level of dental and oral health in Indonesia is still relatively low. This study aims to analyze the dental and oral health of elementary school students at the Tembilahan Hulu Community Health Center, Indragiri Hilir Regency. This research employs a qualitative method through in-depth interviews, observations, and document review. The research informants were the Head of the Community Health Center and the dentist. Observations were made by directly observing the planning, implementation, and reporting processes, as well as documentation review. The results of the study identified the priority problem, which was the high number of dental caries cases in school-age children at the Tembilahan Hulu Community Health Center. The causes were limited human resources for implementing the dental and oral health program, non-functioning counseling and mass tooth brushing, lack of educational media, incomplete School Dental Health (UKGS) KIT, no Health Operational Assistance funds for the UKGS program, lack of knowledge and awareness of the importance of dental and oral health, and the family environment having incorrect habits such as improper tooth brushing. It is recommended for the Community Health Center to attend dental and oral health training, create educational videos on Instagram, and optimize the budget for activities such as counseling and mass tooth brushing.